Inflammatory bowel disease: perceived impact on leisure-time activities - Mattila Kalle; Rankala Rasmus; Voutilainen Markku; Mustonen Anssi (Taylor and Francis [Commercial Publisher], 2022)
Objective: Inflammatory bowel disease, consisting of Crohn's disease and ulcerative colitis, is known to negatively impact an individual's quality of life. Leisure-time activities are an important part of life by creating and strengthening social networks. The aim of this study was to thoroughly evaluate the perceived impact of inflammatory bowel disease on leisure-time activities by quantifying limitations in activities caused by the disease.
Methods: A structured questionnaire, hospital records and national registers were combined to assess limitations caused by the disease in a patient's leisure-time activities. The final study sample was 561 patients.
Results: More than half of the patients (52.8%) reported that IBD had caused limitations in their leisure-time activities. Women perceived that their limitations were greater when compared to the reports by men. One-third of the patients (33.3%) reported reducing and 17.6% abandoning at least one leisure-time activity due to their disease. Most often mentioned activities that were reduced and abandoned were physical activities. The IBDQ32 score had a significant correlation with all of the studied outcomes. Laboratory tests results and the patient's age or the level of income did not correlate with limitations in leisure-time activities.
Conclusions: In conclusion, this study showed that patients with inflammatory bowel disease perceived a marked limitation in their leisure-time activities due to their disease.